Respuesta :
point slope form:
y - y1 = m(x - x1) where m = slope
in this case y + 2 = -3(x - 5)
slope = - 3
hope it helps
y - y1 = m(x - x1) where m = slope
in this case y + 2 = -3(x - 5)
slope = - 3
hope it helps
Hi !
y + 2 = -3(x - 5)
The general equation for a line is y = m·x + n (where m represents the slope and n represents the intersection with the y axis )
So,express y + 2 = -3(x - 5) as y = -3x + 15 - 2 or y = - 3x + 13
The coefficient of x is -3 so the slope is -3
y + 2 = -3(x - 5)
The general equation for a line is y = m·x + n (where m represents the slope and n represents the intersection with the y axis )
So,express y + 2 = -3(x - 5) as y = -3x + 15 - 2 or y = - 3x + 13
The coefficient of x is -3 so the slope is -3